2020
DOI: 10.1186/s12943-020-01161-1
|View full text |Cite|
|
Sign up to set email alerts
|

m6A demethylase ALKBH5 inhibits tumor growth and metastasis by reducing YTHDFs-mediated YAP expression and inhibiting miR-107/LATS2–mediated YAP activity in NSCLC

Abstract: Background: The importance of mRNA methylation erased by ALKBH5 in mRNA biogenesis, decay, and translation control is an emerging research focus. Ectopically activated YAP is associated with the development of many human cancers. However, the mechanism whereby ALKBH5 regulates YAP expression and activity to inhibit NSCLC tumor growth and metastasis is not clear. Methods: Protein and transcript interactions were analyzed in normal lung cell and NSCLC cells. Gene expression was evaluated by qPCR and reporter ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
227
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(236 citation statements)
references
References 75 publications
(129 reference statements)
8
227
1
Order By: Relevance
“…Another study by Jin et al suggested that ALKBH5 inhibited tumor growth and metastasis in vivo by reducing the expression and activity of YAP. 17 Consistent with these studies, the results of our study showed that ALKBH5 is underexpressed in ESCA tissues, and low expression of ALKBH5 was associated with poor survival, indicating that ALKBH5 might act as a tumor suppressor gene in ESCA.…”
Section: Discussionsupporting
confidence: 91%
“…Another study by Jin et al suggested that ALKBH5 inhibited tumor growth and metastasis in vivo by reducing the expression and activity of YAP. 17 Consistent with these studies, the results of our study showed that ALKBH5 is underexpressed in ESCA tissues, and low expression of ALKBH5 was associated with poor survival, indicating that ALKBH5 might act as a tumor suppressor gene in ESCA.…”
Section: Discussionsupporting
confidence: 91%
“…However, Tang et al uncover the tumor suppressive function of ALKBH5 through m 6 A-dependent inactivation of Wnt signaling [34]. In addition, ALKBH5 inhibits tumor growth and metastasis via abolishing expression and activity of YAP in non-small cell lung cancer [35]. And our findings also clarify that ALKBH5 inhibits HCC malignancy through impairing the expression of LYPD1.…”
Section: Discussionsupporting
confidence: 61%
“…For example, m 6 A demethylase ALKBH5 (m 6 A eraser) has been shown to inhibit tumor growth and metastasis by reducing YTHDFs-mediated YAP expression and inhibit miR-107/ LATS2-mediated YAP activity in NSCLC. 21 Another m 6 A methyladenosine METTL3 (m 6 A writer) induced miR-143-3p has been reported to promote the brain metastasis of lung cancer via regulation of VASH1. 22 In addition, Liu et al demonstrated that m 6 A demethylase FTO (m 6 A eraser) promotes cell proliferation and invasion in lung squamous cell carcinoma by regulating MZF1 expression.…”
Section: Discussionmentioning
confidence: 99%